Thermal conductivity enhancements of ironoxide graphene hybrid nanofluids - Arifutzzaman, A.K.H.A. Ma
Heat transfer fluids (HTFs) have characteristically poor heat transfer transport efficiency due to their low thermal conductivities (TC’s) which significantly limits their application as coolant in modern high-tech industries. A number of studies have been conducted using ironoxide particle dispersed nanofluids to expand the TC of HTFs. However, due to the necessity of large quantities of heat transfers, ironoxide nanofluids are not a very widespread solution for wide usage. Incorporation of high thermal conductive material in a nanofluid enhances the TC of the prepared hybrid nanofluid. Graphene (Gr) is the most comparable carbon-based nanomaterial, due to its exponentially high TC and enormously large surface area with negligible thickness. Therefore, the main aim of this research study was to evaluate the TC enhancements of the developed novel ironoxide-Gr hybrid nanofluid system. In this purpose, at the first phase, the TC of deionized water (DW) based maghemite (MH) ironoxide nanoparticle dispersed (MH/DW) nanofluids was investigated. Spherical shape MH nanoparticles were successfully synthesized using the wet chemical co-precipitation technique with the average crystallite size of around 20 nm. Results showed that MH/DW nanofluids exposed very good stability against sedimentation. The maximum TC enhancement of MH/DW nanofluids was perceived for the MH concentration of 0.157 mg/ml among the analyzed samples. At 25 oC, it provided ~ 4.5 % enhancements of the TC over the DW and then it reached to about ~ 32 % in 60 oC temperature. In the second phase, systematic TC analysis of exfoliated Gr dispersion in DW was conducted separately with increasing temperatures. Few layered Gr flakes were effectively processed using sonication assisted liquid phase exfoliation (LPE) technique separately in two different solvents, N-Methyl-2-Pyrrolidone (NMP) and N, N-dimethylformamide (DMF) with a systematic centrifugation (500 - 4000 rpm) scheme. For the fixed time of sonication, minimum values of ID/IG (ratios of D and G peak intensity in Raman spectrum) were found for 500 rpm which were 0.697 and 0.879 for the exfoliated Gr in NMP (Gr-NMP) and exfoliated Gr in DMF (Gr-DMF) respectively. The exfoliated Gr-NMP and Gr-DMF dispersions in DW with the same amount loading showed that, 500 rpm samples exhibited the maximum TC as compared to the higher centrifuge speeds in all the tested temperatures. In the third phase, MH nanoparticle and Gr-NMP dispersed hybrid nanofluids (Gr-NMP/MHDW) of different compositions with varying concentration ratios (from 1:0.3 to 1:0.9) were successfully developed using a solvo-thermal two-steps approach. Stability monitoring showed that the maximum precipitation rate was ~ 8.4 % for hybrid nanofluids sample with the concentration ratio of 1:0.9 after 600 hours. Evaluation of the TC enhancements revealed that, the effect of the addition of Gr was lower than the effect of temperature on the TC enhancements of Gr-NMP/MH-DW hybrid nanofluid samples over the MH-DW base fluid. Where, temperature of 50 oC was found be critical in terms of percentage of the TC enhancements over MH-DW base fluid. The maximum enhancement of TC was attained ~ 43 % at 25 oC and it reached at almost 103 % at 60 oC temperature for hybrid nanofluid sample with the concentration ratio of 1:0.9. In the hybrid nanofluid system, the effect of Gr was much prominent than that of the effect of MH nanoparticle in terms of TC enhancement. The effective TC of produced nanofluids was predicted with the theoretical modelling. Prediction of effective TC enhancements by Maxwell-Garnet type effective medium approximation (MG-EMA) model exposed that, the enhancement of TC of MH/DW nanofluids was contributed by both of the static and dynamic mechanisms of the MH nanoparticles. Execution of modified MG-EMA type models in Gr flake dispersed nanofluids revealed that, Gr flakes’ extremely wide basal plane compared to the negligible thickness and its non-flatness or crumpled geometry have the leading impacts on the effective TC properties of nanofluids. It is seen that, for the crumpled factor of approximately 0.205 the predicted effective TC enhancements were fairly agreed the experimental TC’s of Gr flake dispersed nanofluids. Taken together, the developed hybrid nanofluid system could provide a significant potential and regard as an attractive solution for the next-generation materials for heat transfer application as coolant and lubricant fluids.